2011
DOI: 10.1189/jlb.0511244
|View full text |Cite
|
Sign up to set email alerts
|

Higher proportions of circulating FOXP3+ and CTLA-4+ regulatory T cells are associated with lower fractions of memory CD4+ T cells in infants

Abstract: FOXP3+ and CTLA-4+ Tregs may modulate CD4+ T-cell activation and homing receptor expression in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 38 publications
(56 reference statements)
5
29
0
Order By: Relevance
“…However, recent discoveries indicate that infant hyporesponsiveness is largely modulated by T regulatory cells. In fact, infants have a higher proportion of T regulatory cells but a lower proportion of T follicular helper cells than adults (12). Infants have lower numbers of circulating CD4 ϩ CCR5 ϩ T cells, the main target for HIV (13), although a high proportion of CD4 ϩ…”
Section: Early Life and Adult Immune Responsesmentioning
confidence: 99%
“…However, recent discoveries indicate that infant hyporesponsiveness is largely modulated by T regulatory cells. In fact, infants have a higher proportion of T regulatory cells but a lower proportion of T follicular helper cells than adults (12). Infants have lower numbers of circulating CD4 ϩ CCR5 ϩ T cells, the main target for HIV (13), although a high proportion of CD4 ϩ…”
Section: Early Life and Adult Immune Responsesmentioning
confidence: 99%
“…Fecal samples, which were obtained at 1, 2, 4, and 8 wk of age, were cultured quantitatively for major groups of aerobic and anaerobic bacteria, as previously described (18). In brief, staphylococci were isolated on Staphylococcus agar and identified as Staphylococcus aureus or coagulasenegative staphylococci with the coagulase test.…”
Section: Sampling and Culturing Of The Gut Microbiotamentioning
confidence: 99%
“…Allophycocyanin-and FITC-conjugated mouse Ig G 1 isotype controls (clone 340, allophycocyanin IgG 1 1/90 and FITC IgG 1 1/20; BD Bioscience) were used as references when gating on the CD5 + and CD27 + populations within the CD20 + lymphocyte population. As previously described (18), the gate for FOXP3 was set by comparing the expression of FOXP3 within the CD25…”
Section: Cd25mentioning
confidence: 99%
“…If this is the case, cytokine responses to antigens in cord blood might have little relevance to immune responses to the same antigens later in childhood. 131 The frequency of regulatory T cells at birth is inversely associated with gestational age 130,[132][133][134][135] and this difference may persist for a significant period into infancy. Findings from our laboratory have suggested that the allergen reactivity of neonatal T cells consists predominantly of a default response by recent thymic emigrants, which provide an initial burst of short-lived cellular immunity in the absence of conventional T cell memory.…”
Section: Surface Phenotype Of T Cells In Early Lifementioning
confidence: 99%